A decade of next‐generation sequencing in genodermatoses: the impact on gene discovery and clinical diagnostics. (1st February 2021) - Chiu, F.P.‐C.; Doolan, B.J.; McGrath, J.A.; Onoufriadis, A.
Summary: Background: Discovering the genetic basis of inherited skin diseases is fundamental to improving diagnostic accuracy and genetic counselling. In the 1990s and 2000s, genetic linkage and candidate gene approaches led to the molecular characterization of several dozen genodermatoses, but over the past decade the advent of next‐generation sequencing (NGS) technologies has accelerated diagnostic discovery and precision. Objectives: This review examines the application of NGS technologies from 2009 to 2019 that have (i) led to the initial discovery of gene mutations in known or new genodermatoses and (ii) identified involvement of more than one contributing pathogenic gene in individuals with complex Mendelian skin disorder phenotypes. Methods: A comprehensive review of the PubMed database and dermatology conference abstracts was undertaken between January 2009 and December 2019. The results were collated and cross‐referenced with OMIM. Results: We identified 166 new disease–gene associations in inherited skin diseases discovered by NGS. Of these, 131 were previously recognized, while 35 were brand new disorders. Eighty‐five were autosomal dominant (with 43 of 85 mutations occurring de novo ), 78 were autosomal recessive and three were X‐linked. We also identified 63 cases harbouring multiple pathogenic mutations, either involving two coexisting genodermatoses ( n = 13) or an inherited skin disorder in conjunction with other organ system phenotypes ( n = 50). Conclusions: NGS technologies have accelerated disease–gene discoveries in dermatology over the last decade. Moreover, the era of NGS has enabled clinicians to split complex Mendelian phenotypes into separate diseases. These genetic data improve diagnostic precision and make feasible accurate prenatal testing and better‐targeted translational research. Abstract : What is already known about this topic? Making an accurate diagnosis of an inherited skin disease can be challenging, and genetic testing is a valuable part of patient evaluation. Next‐generation sequencing has the potential to improve and refine how new disease genes are discovered and to demonstrate how mutations in more than one gene can be clinically significant. What does this study add? Between 2009 and 2019, next‐generation sequencing was used to discover 166 new inherited skin disease–gene associations, and to characterize 63 cases of multiple gene pathologies contributing to complex inherited skin disease phenotypes. Approximately 90% of the discoveries were made using whole‐exome sequencing. The advent of next‐generation sequencing technologies, such as whole‐exome sequencing, has accelerated and improved diagnostic accuracy for genodermatoses.